Genotyping, in silico screening and molecular dynamics simulation of SNPs of MGMT and ERCC1 gene in lung cancer patients treated with platinum-based doublet chemotherapy - Singh, Sidhartha; Gupta, Anu; Singh, Navneet; Sengupta, Parth Sarthi; Panda, Saroj Kumar; Sharma, Siddharth (Journal of biomolecular structure & dynamics, 2024)
Lung cancer, the leading cause of death worldwide, arises from an intricate combination of genetic and environmental factors. Genetic variations can influence the chemotherapeutic response of lung cancer patients in DNA repair genes. This study examines the response to platinum-based drugs among lung cancer patients of North Indian descent who possess genetic variations in the MGMT and ERCC1 genes. P CR-RFLP method was used for genotypic analysis. MedCalc statistical software was used to calculate odds ratios and Median Survival Time (MST). GROMACS software was used to perform Molecular dynamic simulation. ADCC Patients revealed a significant association with MGMT in the heterozygous genotype (HR= 1.56, p=0.02) and also with ERCC1 in both mutant and combined variants (HR= 1.25, p=0.01; HR=0.78, p=0.03). SQCC subjects harbouring ERCC1 polymorphism also reported a 2-fold increase in hazard ratio and a corresponding decrease in survival time for heterozygous and combined variants (HR= 2.55, p=0.02; HR 2.33, p=0.01, respectively). MD simulation results demonstrate a lower RMSD, stable radius of gyration, and lower RMSF, indicating the mutated MGMT protein is more stable than the wild. Further, the docking score for DNA-Wild and DNA-L84F mutants are -201.6 and -131.8, respectively. MD Simulation of the complexes further validated the results. Our study concludes that MGMT and ERCC1 polymorphisms are associated with decreased overall survival. Further, computational analysis of MGMT (rs12917) polymorphism revealed that mutated MGMT cannot bind properly to the DNA and hence cannot properly repair DNA, resulting in lower overall survival. Communicated by Ramaswamy H. Sarma